Acid- and Volume-Sensitive Chloride Currents in Human Chondrocytes - Kittl, Michael; Winklmayr, Martina; Helm, Katharina; Lettner, Johannes; Gaisberger, Martin; Ritter, Markus; Jakab, Martin (Frontiers in Cell and Developmental Biology, 2020)
Chondrocytes face extreme alterations of extracellular osmolarity and pH, which force them to appropriately regulate their cell volume (CV) and cellular pH. Perturbations of these mechanisms lead to chondrocyte death and ultimately to osteoarthritis (OA), the most common chronic joint diseases worldwide. OA hallmarks are altered cartilage hydration, joint severe fluid acidification, chondrocyte swelling and chondroptosis. Impaired CV regulation and acidotoxicity contribute to disease progression and volume-sensitive anion channels are upregulated in OA. This study assessed the effect of hypotonicity and extracellular acidification on chondrocyte Cl- conductances and CV regulation. Cl- currents and membrane potentials were measured in human C28/I2 cells and primary human chondrocytes using the patch clamp technique. Intracellular pH was assessed by BCECF fluorescence, CV measurements were performed using the Coulter method and cell viability/cell death by a resazurin assay. Hypotonic cell swelling caused activation of a volume-sensitive outwardly rectifying (VSOR) Cl- current followed a regulatory volume decrease (RVD), which was attenuated by the Cl- channel blocker DCPIB. Extracellular, but not intracellular acidification to pH ≤ 5.0 elicited an acid-sensitive outwardly rectifying (ASOR) Cl- conductance. Activation of either current depolarized the cell membrane potential. Under simultaneous hypotonic and acidic stimulation, VSOR and ASOR currents transiently coactivated, giving rise to a mixed current phenotype. Over time the VSOR current gradually vanished and the residual conductance showed a pure ASOR current phenotype. Extracellular acidification caused an isotonic CV gain and a complete suppression of RVD under hypotonic conditions. The results suggest that inactivation of the VSOR current under acidic conditions impairs CV regulation in chondrocytes, which is likely to compromise chondrocyte viability.